Feminists eminists at the World Social Forum: Challenges for a New Political Culture - Lilian Celiberti; Virginia Vargas (Revista Estudos Feministas, 2003)
The article deals with the ways of incursion of the feminist plurality’s significant expressions in the World Social Forum. These incursions express the changes in the subjectivities and in strategies of struggle that feminist movements in particular and social movements in general begin to develop, in the frame of a globalised world and in the new millennium. It’s an unprecedented process, that is promoting the development of new paradigms for collective action, that combines local and global issues, the interconnection of multiple agendas and the recovery of a more profound dimension of economic, social, cultural and symbolic justice, broadening, in this process, the concept of politics, the political and the power. The article sets discussion around the ways in which social movements converging in the Forum – that drag old dynamics and at the same time recreate new paradigms – work in politics and open the possibility of re-inventing an emancipation map and a social conception, capable of competing with neo-liberal consensus and with the single thought, recuperating diversity and plurality of social individuals and actors.